1995
DOI: 10.1143/jjap.34.1723
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Stability of HBF4-Treated (100)Si Surfaces

Abstract: Si(100) surfaces were modified by means of enhanced RCA procedure with “ HBF4-last” and “HF-last”. Nulling ellipsometric (NE) and secondary ion mass spectrometric (SIMS) measurements revealed that HBF4-treated Si surface is more strongly passivated by hydrogen and fluorine than HF-treated one: the oxidation rate of the HBF4-treated Si surfaces in air was found to be lower than that of the HF-treate surface. Scanning tunneling microscope (STM) images of HBF4-cleaned surface after 18 h storage in air were qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Hydrophobicity and hydrophilicity have been identified with the existence of certain chemical species on the surface: 27 The origin of hydrophilicity is singular and associated OH groups on the Si surface, while hydrophobic surfaces are mainly characterized by Si-H and probably also O and C in minor quantities. SIMS analysis indicated 8 bonds clearly exist on HBF 4 -treated surfaces. Hence it is likely that the Si-F bond should be the cause for hydrophilicity.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Hydrophobicity and hydrophilicity have been identified with the existence of certain chemical species on the surface: 27 The origin of hydrophilicity is singular and associated OH groups on the Si surface, while hydrophobic surfaces are mainly characterized by Si-H and probably also O and C in minor quantities. SIMS analysis indicated 8 bonds clearly exist on HBF 4 -treated surfaces. Hence it is likely that the Si-F bond should be the cause for hydrophilicity.…”
Section: Discussionmentioning
confidence: 97%
“…Such adsorbed chemical species may affect the ellipsometric data and result in modification of the dielectric function. 8,14,25,26 The different ͗⑀ 2 ͑E 2 ͒͘ values may correspond to the different numbers of H ͑F͒ atoms adsorpted on the chemically treated surfaces. Our ͗⑀ 2 ͑E 2 ͒͘ results can suggest an order for the number of the adsorbed H ͑F͒ species,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5) Recently, several authors have reported that treatment with aqueous HBF 4 solution results in the removal of the surface native oxide and may leave behind the silicon surface terminated by atomic hydrogen and fluorine. [6][7][8] The fluorine species were identified by secondary-ion mass spectroscopy 6) and X-ray photoelectron spectroscopy (XPS). 8) It has also been shown 8,9) that aqueous NH 4 BF 4 and H 2 SiF 6 solutions can etch-remove the silicon native oxide and leave behind a shiny flat surface.…”
Section: Introductionmentioning
confidence: 99%